The moderating effect of constraints between entrepreneurial determinants and the success of female entrepreneurship - BARHOUM , Nesrine; BOUDABBOUS , Sami (Revue Internationale des Sciences de Gestion, 2025)
The paper highlights the impact of women's entrepreneurship on economic development, job creation, and reducing gender inequality. Despite increasing education and skills among women, they still face systemic constraints limiting their entrepreneurial potential. The research includes a sample of 100 women entrepreneurs, selected through stratified sampling for diversity in sector of activity, education level, and location. Results show that while access to finance has a positive impact, it remains marginal. Education level is strongly correlated with entrepreneurial commitment, and social support is crucial for women-led business success. Gender stereotypes exacerbate challenges faced by women. This research enriches literature on women's entrepreneurship by emphasizing interactions between determinants and constraints, providing data for effective policy-making. It underscores the need for supportive environments and combating gender stereotypes to empower women entrepreneurs.